Two new species of Protonemura (Plecoptera: Nemouridae) from China, with biogeographical notes on the genus - Li, Weihai; Murányi, Dávid; Yang, Ding (Zootaxa, 2017)
Two new species of the genus Protonemura (Plecoptera: Nemouridae: Amphinemurinae) are described from China, P. bifurcata sp. n. from a holotype male from Taiwan and P. datongensis sp. n. from males and females collected in Datong County of the high altitude Tibetan Plateau of Qinghai Province, China. The new taxa are compared with related congeners respectively. A new combination, Indonemoura filigera (Kawai) comb. n, is proposed for Protonemura filigera Kawai, 1969. The distribution of Protonemura in the East Palaearctic and the Oriental Region is discussed and mapped.